Stent fracture as a complication of superficial femoral artery stenting - a case report - Jędrzej Tkaczyk; Michał Terpiłowski; Klaudia Brożyna; Katarzyna Baltaziak; Barbara Klatka; Jan Jakub Kęsik; Marek Iłżecki (Kazimierz Wielki University, 2019)
Introduction: Peripheral artery disease (PAD) is an atherosclerotic vascular disease that results in obstruction of blood flow in the arteries other than those in the coronary circulation. PAD is often located in lower extremities, with patients presenting symptoms of intermittent claudication or critical lower limb ischemia. Angioplasty and stent implantation are often used in the treatment of PAD. Although these methods are considered as a low invasive and low risk, some factors may limit stent patency in the future. The fracture of the implanted stent may be one of these. Case report: A 68 old man, long-term smoker, with a history of chronic limb ischemia and many vascular surgeries because of PAD was admitted to the hospital with symptoms of the acute limb ischemia. Angiography showed a fracture of the stent implanted during the earlier hospitalization, with a fragment displacement to the left external iliac artery. The patient was successfully treated with catheter-directed thrombolysis. Discussion: Stent fracture is usually asymptomatic, however, it may cause complications, such as restenosis, pseudoaneurysm, perforation of the vessel, and in-stent embolism. The cumulative incidence of the femoropopliteal stent fracture varies from 2 to 65% in several studies. Incidence increases with stent length and is significantly lower in the second generation of nitinol stents, that was designed to have enhanced flexibility and durability.